2012
DOI: 10.4161/cc.21262
|View full text |Cite
|
Sign up to set email alerts
|

The role of mTOR signaling pathway in spinal cord injury

Abstract: T he mammalian target of rapamycin (mTOR) signaling pathway plays an important role in multiple cellular functions, such as cell metabolism, proliferation and survival. Many previous studies have shown that mTOR regulates both neuroprotective and neuroregenerative functions in trauma and various diseases in the central nervous system (CNS). Recently, we reported that inhibition of mTOR using rapamycin reduces neural tissue damage and locomotor impairment after spinal cord injury (SCI) in mice. Our results demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
62
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 75 publications
1
62
0
1
Order By: Relevance
“…The mTOR inhibitors have been used as immunosuppressants in patients undergoing transplantation surgery, and have also been used as anticancer agents . In addition, many previous experimental studies using CNS injury models have demonstrated promising effects of mTOR inhibition to reduce neural tissue damage . The present study suggests that the inhibition of mTOR has a significant therapeutic effect that can improve locomotor function and neuropathic pain condition following SCI.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The mTOR inhibitors have been used as immunosuppressants in patients undergoing transplantation surgery, and have also been used as anticancer agents . In addition, many previous experimental studies using CNS injury models have demonstrated promising effects of mTOR inhibition to reduce neural tissue damage . The present study suggests that the inhibition of mTOR has a significant therapeutic effect that can improve locomotor function and neuropathic pain condition following SCI.…”
Section: Discussionmentioning
confidence: 52%
“…The mTOR pathway also regulates the immune function and autophagy . In addition, many previous studies have shown that mTOR regulates both neuroprotective and neuroregenerative functions in trauma and various diseases of the central nervous system (CNS) …”
mentioning
confidence: 99%
“…Several recent studies have focused on the usefulness of autophagy as a therapy for inflammation‐induced disease . Increases in the expression levels of autophagic markers have been detected following ischaemia/reperfusion or inflammation injury, indicating that injury or stress can trigger cell self‐protective mechanisms by activating autophagy . In contrast, other studies have shown that autophagy has pernicious effects .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Park et al [26] reported that rapamycin protected human neuroblastoma SH-SY5Y cells against fipronil-induced apoptotic cell death. Kanno et al [18] found that rapamycin reduced locomotor impairment and neuronal death after spinal cord injury in mice. This effect of rapamycin was reported to be mediated through activation of autophagy by inhibiting the mammalian target of rapamycin (mTOR) signaling pathways [36].…”
Section: Introductionmentioning
confidence: 99%